Forecasting the Tendencies of Socio-Economic Development in Poland on the Basis of the Level of Income Inequalities Using the VAR Model - Litwiński , Michał (Studia Oeconomica Posnaniensia, 2017)
Recently, there has been observed intensified considerations on socioeconomic development and its relationship with income inequalities in Poland. There exists also a need to forecast the tendencies further. The scientific problem of the paper concerns the possibilities to predict socio-economic development on the basis of the level of income inequalities in Poland. The aim of the research in the paper is to propose using the VAR model that could be a basis for predictions in that scope. A model was estimated using data for the years 2004-2014. Socio-economic development was forecasted for the years 2015-2017.